Atrial septal defect as a cause of chronic cough and recurrent infections in a 4-year-old boy - Piotr Fuss (Pediatria i Medycyna Rodzinna, 2017)
Recurrent infections of the respiratory system among children are the most common reason for ambulatory treatment and one of the main causes of hospitalisation. Out of many factors that can be potentially responsible for the recurrent infections in children it is necessary to consider the ones that are connected with the immaturity of the immune system of a child and ones that can disturb the proper functioning of this system. It seems that the most important observations are those pointing at links between recurrent infections of the respiratory tract and the allergic process. The present article describes a case of a boy with recurrent respiratory infections, who was diagnosed towards immune system malfunction and allergies. An echocardiographic examination revealed a major defect of the interatrial septum. This  heart condition was treated with cardiac surgery as a result of which infections occur less frequently and do not require the hospitalisation of the patient.